Compositional and functional dynamics of dried papaya as affected by storage time and packaging material - Udomkun, Patchimaporn; Nagle, Marcus; Argyropoulos, D.; Mahayothee, B.; Latif, S.; Müller, Joachim (Elsevier, 2016)
Papaya has been identified as a valuable source of nutrients and antioxidants, which are beneficial for human health. To preserve the nutritional properties after drying, appropriate storage specifications should be considered. This study aimed to investigate the quality and stability of air-dried papaya in terms of quality dynamics and behavior of bio-active compounds during storage for up to 9 months in two packaging materials: aluminum laminated polyethylene and polyamide/polyethylene. Samples with moisture content (MC) of 0.1328 g g−1 and water activity (aw) of 0.5 were stored at 30 °C and relative humidity (RH) of 40–50%. The MC, aw, degree of browning (DB) and 5-hydroxymethylfurfural (HMF) content were found to notably increase as storage progressed. On the contrary, there was a significant decrease in antioxidant capacity (DPPH, FRAP and ABTS), total phenolic (TP) and ascorbic acid (AA) contents. Packaging in aluminum laminated polyethylene under ambient conditions was found to better preserve bio-active compounds and retard increases in MC, aw and DB, when compared to polyamide/polyethylene.